Job Demands, Job Resources, and Work Engagement among Shift Workers in the Culinary Service Sector - Nabila Iftah Rizqia; Benny Bernadus (International Journal of Marketing & Human Resource Research, 2026)
This study examines work engagement among shift workers in the culinary service sector by focusing on how employees respond to demanding work conditions and the availability of supportive job characteristics. Drawing on the Job Demands Resources framework, the research addresses whether engagement in high intensity service work is shaped more strongly by work pressures or by the presence of enabling resources in the workplace. Data were collected from 85 shift employees working in culinary outlets in South Bandung, Indonesia, using a structured questionnaire and a purposive sampling approach. Quantitative analysis was conducted through descriptive statistics, correlation analysis, and multiple linear regression. The findings reveal that job resources are a significant and positive predictor of work engagement, whereas job demands do not show a statistically meaningful effect when both variables are analyzed simultaneously. The regression model explains approximately one quarter of the variance in work engagement, indicating that employees’ psychological involvement in their work is influenced primarily by supportive conditions rather than by the intensity of job demands. These results highlight the importance of autonomy, social support, performance feedback, developmental opportunities, and coaching in sustaining engagement among shift workers operating under demanding service conditions. Practically, the study suggests that strengthening job resources is a more effective strategy for enhancing engagement and ensuring workforce sustainability in the culinary industry than focusing solely on reducing work demands.